Стратегия РФ в азиатско-тихоокеанском регионе (ՌԴ ռազմավարությունը Ասիա-Խաղաղօվկիանոսյան տարածաշրջանում արդի փուլում) - Բալասանյան, Գրիգոր (YSU Journal of International Affairs, 2016)
The quickly developing Asia-Pacific region represents itself as an interest and importance in the 21st century. Not as other countries do, RF always takes part in ascertaining an economic and political influence in the region taking into the consideration the fact that the main part of the RF is located in that region. Thestudy is divided into 2 parts – the activity of the RF authorities in participating the regional integrative organizations, and the problems, connected with the development of the strategy, that exist in the region.
Keywords: strategy, RF, APR, APEC, ASEAN, USA, China